DESCRIPTION OF OSTEOPOROSIS RISK BASED NUTRITION STATUS IN ELDERLY AND CALCIUM INTAKE IN PUSKESMAS SIDOSERMO SURABAYA 2015 - Prabawani, Yuni (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2015)
Background. The number of elderly in Indonesia in 2011 about 24 million people, or nearly 10% of the population. Experts projected that by 2020, life expectancy was 71.7 years with the elderly into estimates of the number of elderly 28.8 million people (11.34%). An increase in the number of elderly will cause problems in the elderly, especially the problem of degenerative diseases, one of them is osteoporosis. Prevalence rate of osteoporosis is higher so the need for vigilance. Causes Osteoporosis is multifactoral, such as unhealthy lifestyle and not exercising regularly, as well as the prevention of osteoporosis knowledge is lacking. The occurrence of Osteoporosis caused by lack consumption of calcium in Indonesian society. The purpose of this research was to describe the risk of osteoporosis by nutritional status and calcium intake in the elderly in health centers Sidosermo Surabaya 2015. Methodology This study is a descriptive study with cross sectional approach. A total of 28 elderly people (samples) with a total sampling method. Body weight was measured by digital scale, height was measured by microtoise staturemeter, Osteoporosis was assessed through the measurement of bone density by using Hologic Sahara Densitometry Quantitative Ultrasound (QUS) in the calcaneus bone, which is classified into three is normal, mild risk and high risk. Results: A total of 7 people (25%) had osteoporosis, 21 people had osteopenia (75%). Twelve have a normal body mass index, and 16 had abnormal body mass index. Calcium intake in 8 people (28,6%) had enough calcium intake and 20 people (71,4 %) had low calcium intake.Conclusion: The incidence of osteoporosis in the Health Center Sidosermo Surabaya occurred in elderly with abnormal BMI and inadequate calcium intake.